2010
DOI: 10.1111/j.1539-6975.2010.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Don't They Care? Or, Are They Just Unaware? Risk Perception and the Demand for Long-Term Care Insurance

Abstract: The potential need for long-term care (LTC) is one of the greatest financial risks faced not only by the elderly but also by their adult children, who often provide care or financial assistance. We investigate adult children's role in the demand for LTC insurance. Similar to flood insurance, we find that demand for LTC insurance is low due to low risk perception. The more aware adult children are of the risk, the more likely LTC insurance is to be purchased, either by the children themselves on behalf of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 31 publications
1
53
0
1
Order By: Relevance
“…Empirical surveys confirm such a possibility. Indeed, Zhou-Richter et al (2010) showed that in Germany adult children would be willing to purchase LTC insurance for their parents. For the U.S., Cohen et al (2000) indicated that primary informal caregivers purchased LTC insurance policy themselves for their elderly relatives.…”
Section: Premium Paid By the Childmentioning
confidence: 98%
See 1 more Smart Citation
“…Empirical surveys confirm such a possibility. Indeed, Zhou-Richter et al (2010) showed that in Germany adult children would be willing to purchase LTC insurance for their parents. For the U.S., Cohen et al (2000) indicated that primary informal caregivers purchased LTC insurance policy themselves for their elderly relatives.…”
Section: Premium Paid By the Childmentioning
confidence: 98%
“…In that respect, Zhou-Richter et al (2010) recently investigated empirically the role of adult children in the demand for LTC insurance. They showed that the more aware adult children are of LTC risk, the more likely LTC insurance is purchased, either by the adult children themselves on behalf of their parents or by the parents under the influence of their adult children.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the interpretation of (22) is similar to that of (25) except that the signs of the two effects are reversed.…”
Section: Optimal Policy: Problem and First-order Conditionsmentioning
confidence: 85%
“…Our approach is compatible with similar studies such as Ferna´ndez and Forder (2010) for the U.K. 13 See, for example, Jagger et al (2006). 14 See Pauly (1990) and Zhou-Richter et al (2010).…”
Section: Risk Mitigation Of a Protection For Ltc Lifetime Individual mentioning
confidence: 98%